Perceived Effects of Adoption of Recommended Practices among Rural Farmers of Nigeria - Usman, Mohammed; J J Pelemo (Journal of Extension Education, 2020)
The study assessed the perceived effects of recommended practices on levels of hygienic practices, health-care Expenditure, and productive time for Agricultural Activities and children school attendances among the rural farmers in Mokwa Local Government area of Niger State, Nigeria. Multi-stage sampling technique was used to select 311 of rural populace. Data were collected using structured questionnaire as well as interview schedule and analyzed using descriptive statistics. The mean age of the respondents was 46 years while the mean household size was 9 persons. Also, the mean years of experience was 20.8 years while 41.4% of the respondents had primary education. The mean household income was Nigerian Naira N175,500.00. The serious constraints to adoption of recommended practices were bad attitude and lack of credit facilities It is recommended that environmental health workers should be empowered to enforce sanctions on noncompliance with adoption of recommended practices and efforts should be made by stakeholders to sustain this channel of sensitization.